Socioeconomic Status, Culture, and Reading Comprehension in Immigrant Students - Ibáñez-Alfonso, Joaquín A.; Hernández-Cabrera, Juan Andrés; Duñabeitia, Jon Andoni; Estévez, Adelina; Macizo, Pedro; Bajo, María Teresa; Fuentes, Luis J.; Saldaña, David (Frontiers in Psychology, 2021)
Research on reading comprehension in immigrant students is heterogeneous and conflicting. Differences in socioeconomic status and cultural origins are very likely confounds in determining whether differences to native pupils can be attributed to immigrant status. We collected data on 312 Spanish students of Native, of Hispanic origin–therefore with the same family language as native students- and Non-Hispanic origin, while controlling for socioeconomic status, nonverbal IQ and school membership. We measured reading comprehension, knowledge of syntax, sentence comprehension monitoring, and vocabulary. Differences among groups appeared only in vocabulary and syntax (with poorer performance in the non-Hispanic group), with no differences in reading comprehension. However, regression analyses showed that most of the variability in reading comprehension was predicted by age, socioeconomic status, nonverbal reasoning, and comprehension monitoring. Group membership did not significantly contribute to explain reading comprehension variability. The present study supports the idea that socioeconomically disadvantaged students, both native and immigrants from diverse cultural backgrounds, irrespective of the language of origin, are probably equally at risk of poor reading comprehension.